Smart sensing systems for in-home health status and emotional well-being monitoring during COVID-19 - Izdrui, D. (2022)
The COVID-19 pandemic has restricted the mobility of the population. The experts propose several solutions in order to decrease the number of patients infected with this new virus by treating and monitoring them within the comfort of their own home. A new direction for the research has been identified including healthcare smart sensing systems which can provide medical diagnoses, surveillance, and treatment partially or totally remotely. The field of wearable, smart sensing solutions is becoming nowadays a widely accepted solution characterized also by the increased level of acceptance with regard to home health status monitoring. Pervasive computing and wearable solutions are frequently a topic included in current projects and are expected in new future developments, particularly in the pandemic context which forces people to remain mostly at home. As part of wearable devices the design of textiles, computer science, and smart materials are the three major development directions. The latest developments associated with the monitoring of health status and emotional well-being are presented and discussed in this chapter.